1996
DOI: 10.1523/jneurosci.16-17-05443.1996
|View full text |Cite
|
Sign up to set email alerts
|

Traffic of Dynamin within IndividualDrosophilaSynaptic Boutons Relative to Compartment-Specific Markers

Abstract: Presynaptic terminals contain several specialized compartments, which have been described by electron microscopy. We show in an identified Drosophila neuromuscular synapse that several of these compartments-synaptic vesicle clusters, presynaptic plasma membrane, presynaptic cytosol, and axonal cytoskeleton-labeled by specific reagents may be resolved from one another by laser scanning confocal microscopy. Using a panel of compartment-specific markers and Drosophila shibire ts1 mutants to trap an intermediate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
136
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(147 citation statements)
references
References 65 publications
11
136
0
Order By: Relevance
“…Perhaps this is the explanation for so-called perforated PSDs observed by electron microscopy (64). Evidence exists for other endocytic hot spots where clathrin (66,67) and dynamin (68,69) have been found to be concentrated, in the latter case in association with DAP160, a member of the intersectin family (70). Because some members of the Shank/ProSAP family, such as Shank2/ProSAP1, are not completely restricted to the PSD, we suggest, finally, that the interactions identified in the current study may serve a more general dynamin-sequestering role.…”
Section: Dynamin-2 Associates With Shank/prosapsmentioning
confidence: 50%
“…Perhaps this is the explanation for so-called perforated PSDs observed by electron microscopy (64). Evidence exists for other endocytic hot spots where clathrin (66,67) and dynamin (68,69) have been found to be concentrated, in the latter case in association with DAP160, a member of the intersectin family (70). Because some members of the Shank/ProSAP family, such as Shank2/ProSAP1, are not completely restricted to the PSD, we suggest, finally, that the interactions identified in the current study may serve a more general dynamin-sequestering role.…”
Section: Dynamin-2 Associates With Shank/prosapsmentioning
confidence: 50%
“…This region has been defined as a distinct synaptic compartment, the endocytic zone, on the basis of light microscopic studies in Drosophila. The dynamin-binding protein Dap160͞intersectin was shown to be accumulated in this region (32), and other endocytic proteins including dynamin and endophilin have been localized to this area in stimulated Drosophila synapses (33,34). Our recent immunogold studies in lamprey synapses have shown that dynamin can be detected in the endocytic zone after stimulation (E. Evergren, N.T., H. Gad, P.L., L.B., and O.S., unpublished observations).…”
Section: Discussionmentioning
confidence: 98%
“…demonstrate that syt-eGFP is specifically present in SVs, we took advantage of a dynamin mutant shi ts to drive fusion in the absence of vesicle recycling (Estes et al, 1996). shi ts mutants block SV endocytosis at restrictive temperature (35°C), causing SV proteins to trap in the plasma membrane.…”
Section: Figmentioning
confidence: 99%
“…Scale ϭ 5 m. C: Syt-eGFP and endogenous syt localizes to the peripheral of NMJ synapses when exocytosis was stimulated with high [K ϩ ] of 90 mM and endocytosis is blocked under restrictive temperature (35°C, 5 min) in the dynamin mutant background of shi 1 . For a detailed procedure of high [K ϩ ] stimulation of exocytosis and high temperature blockage of endocytosis of NMJ terminals, see Estes et al (1996). The punctate staining nature (shown by arrow) of ␣-syt (in green) or ␣-CSP (in red) is evident and indicated by arrows.…”
Section: Figmentioning
confidence: 99%